2019
DOI: 10.1186/s12891-018-2394-y
|View full text |Cite
|
Sign up to set email alerts
|

Low compartment pressure and myoglobin levels in tibial fractures with suspected acute compartment syndrome

Abstract: BackgroundThe intense ischemic pain of acute compartment syndrome can be difficult to discriminate from the pain related to an associated fracture. Lacking objective measures, the decision to perform fasciotomy is often only based on clinical findings and performed at a low threshold. Biomarkers of muscle cell damage might help to identify and monitor patients at risk. In patients with fractures, however, markers of muscle cell damage could be elevated because of other reasons associated with the trauma, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Blood CK level was significantly higher in the SSI group compared to the non-SSI group. Previous studies have shown that blood CK level may be a marker in diagnosing ACS and evaluating muscle necrosis [ 30 , 31 ]. However, no study shows an association between blood CK levels and SSI.…”
Section: Discussionmentioning
confidence: 99%
“…Blood CK level was significantly higher in the SSI group compared to the non-SSI group. Previous studies have shown that blood CK level may be a marker in diagnosing ACS and evaluating muscle necrosis [ 30 , 31 ]. However, no study shows an association between blood CK levels and SSI.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that high intramuscular pressure coincides with high P-myoglobin levels and that myoglobin may be a relevant, yet unexplored diagnostic tool in ACS associated with trauma. 21 …”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of ACS in the nonobtunded patient is usually made clinically because measurement of compartment pressures with a Stryker (STIC) needle is an invasive, painful procedure that is less than 100% sensitive for detecting ACS. [1][2][3] Recent work performed by Schmidt et al 4 has shown that no value of perfusion pressure from 10 to 30 mm Hg demonstrates the necessary specificity to accurately diagnose compartment syndrome, further calling into question its use as a primary diagnostic measure. Pain with passive stretch, especially pain that is out of proportion to visible injuries, is the ultimate harbinger of ACS.…”
Section: Introductionmentioning
confidence: 99%